A Mathematical Model to Characterize the Role of Light Adaptation in Mammalian Circadian Clock - Shi, Yuzeng; Liu, Yu; Yang, Ling; Yan, Jie (Frontiers in Molecular Biosciences, 2021)
In response to a light stimulus, the mammalian circadian clock first dramatically increases the expression of Per1 mRNA, and then drops to a baseline even the light persists. This phenomenon is known as light adaptation, which has been experimentally proved to be related to the CRTC1-SIK1 pathway in suprachiasmatic nuclei (SCN). However, the role of this light adaptation in circadian rhythm remains to be elucidated. To reveal the in-depth function of light adaptation and the underlying dynamics, we proposed a mathematical model for CRTC1-SIK1 network and coupled it to a mammalian circadian model. The simulation result proved that the light adaptation is achieved by the self-inhibition of CRTC1/CREB complex. Also, consistently with experimental observations, this adaptation mechanism can limit the phase response to short-term light stimulus, and it also restricts the rate of phase shift in a jet lag protocol to avoid overly rapid re-entrainment. More importantly, this light adaptation is predicted to prevent the singularity behavior in cell population, which represents the abolishment of circadian rhythmicity due to desynchronization of oscillating cells. Furthermore, it’s shown to provide refractoriness to successive stimuli with short gap. Therefore, we concluded that the light adaptation generated by CRTC1-SIK1 pathway in SCN provides a robust mechanism, allowing the circadian system to maintain homeostasis in the presence of light perturbations. These results not only give new insights into the dynamics of light adaptation from a computational perspective, but also lead us to formulate hypotheses about the related physiological significance.